Investigasi Intrusi Air Asin di Kawasan Prospek Bijih Besi Pesisir Nusawungu Kabupaten Cilacap Jawa Tengah Berdasarkan Profil Resistivitas-2D - Sehah Sehah; Zaroh Irayani; Sukma Sewiji (Jurnal Fisika FLUX, 2018)
ABSTRACT−Investigation of saltwater intrusion in Nusawungu Coastal area of Cilacap Regency based on the 2D-resistivity data has been done in April – Juni 2018. The resistivity data acquisition has been carried out using Wenner's configuration on four locations covering of the NWT-01, NWT-02, NWT-03, and NWT-04 with a length as 200 meters. The obtained result is the 2D-resistivity profile of subsurface rocks for each trajectory with a depth of about 30 meters. The rock resistivity values which obtained for each trajectory consists of the NWT-01 is 2.30 – 103.00 Ωm; the NWT-02 is 3.65 – 54.30 Ωm; the NWT-03 is 0.96 – 43.20 Ωm; and the NWT-04 is 2.33 – 70.80 Ωm. Based on the interpretation results, the deep aquifer in each trajectory with a resistivity value of 0.96 - 6.81 Ωm are estimated to be intruded by saltwater, while the shallow aquifers have not been significantly intruded by saltwater. Based on the testing results of the electrical conductivity (DHL) of several water samples taken from some wells around the NWT-01 to NWT-04 trajectory, it is known that all of the water is freshwater. Some well water samples have a rather high electrical conductivity value, such as the well A on the NWT-01 with a value of 740.0 μSi/cm and the well C on the NWT-03 with a value of 894.67 μSi/cm. This is thought to be due to the relatively high salt mineral content in the aquifer rocks.